2010
DOI: 10.4081/mr.2010.e6
|View full text |Cite
|
Sign up to set email alerts
|

Type, course and outcome of community acquired infections in hospitalized diabetics

Abstract: Diabetes mellitus has been associated with increased frequency of serious infections which are attributed to immune deficiencies. The aims of this study were to investigate the type, course and outcomes of community acquired infections, and especially bacteremia in diabetics hospitalized for infection. One hundred and thirty-four consecutive patients (67 diabetics and 67 non-diabetics) matched for age, who were admitted to a general District Hospital in Greece due to infection, were included in this case contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Spp., Staphylococcus, Gram negative organism, fungal infection. Eirini et al [3] reported common microorganism in diabetic were Strep. Spp., Klebsiella, E. coli and Fungi.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Spp., Staphylococcus, Gram negative organism, fungal infection. Eirini et al [3] reported common microorganism in diabetic were Strep. Spp., Klebsiella, E. coli and Fungi.…”
Section: Discussionmentioning
confidence: 99%
“…Tuberculosis in diabetic patients is associated with extensive caseation of lung tissue and cavitary lesion with less pleural involvement. [3] Mortality in diabetic patients was due to uncontrolled diabetes, associated comorbid condition and high risk of bacteraemia and septicemia. Miquel et al [4] reported higher mortality 17%.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations